Impact of Instructional Scaffolding Approach on Secondary School Students Achievement in Mathematics - Ihechukwu, Nwoke Bright (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
The study investigated the impact of instructional scaffolding approach on secondary school studentsâ€™ achievement in Mathematics. The study was carried out in Owerri Municipal Council of Imo State. The study was a quasi-experimental research type adopting the pre-test post test non equivalent control design in carrying out the study. A sample of 237 senior secondary school II (SS II) students consisting of 81 males and 156 females was used for the study. The instrument for data collection was a researcher made 30 items objective test questions titled â€œMathematics Achievement Test (MAT)â€. The instrument had reliability coefficient of 0.85 determined using Kuder Richardson 20 formulaÂ (KR20). The experiment group was taught mathematics using instructional scaffolding approach while the control group was taught using traditional approach. The data generated was analyzed using mean and standard deviation to answer research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The result of the study revealed that instructional scaffolding is effective in enhancing secondary school studentsâ€™ achievement in mathematics and minimized gender bias. Based on the result it was recommended that mathematics teachers at secondary school level should apply instructional scaffolding approach in teaching to enhance studentsâ€™ achievement.